Rumanian Folk Music - Bartok, Bela. author. aut Link
769 p.
Keywords: N January 30, 1944, Bela Bart6k, writing from Asheville, North O Carolina, where he had gone to regain his strength after a long period of ill-health in 1943, commented, Here I have started on a very interesting (and, as usual, lengthy) work, the kind I have never done before. Properly speaking, it is not a musical work: I am arranging and writing out fair copies of Rumanian folksong texts'! Although the date has not as yet been established, the first draft of the Rumanian folk texts as texts per se was written-if an apparent age of the MS. can be considered a clue-sometime before Bartok had emigrated to the United States in 1940. This draft (see description below) had been forwarded for etymological data, according to the non-Bart6kian autography appearing thereon. The identity of the informant or informants involved and the circumstances surrounding this matter remain unknown at the present writing. After Bart6k had made offset prints of the music examples of the 2 first two volumes of Rumanian F olk Music in 1940, the printed but incomplete draft of Vol. II (Vocal Melodies)-comprising 304 of the ultimate total of 659 pages-was sent to Nicholas Vama~escu, then di rector of "The Romanian Radio Hour" (Station W. ]. L. B. , Detroit, 3 Michigan), for correction of the texts, in April, 1941. 1 Letter to Joseph Szigeti, in Bartok Bela levelei (ed. Janos Demeny; Budapest: Miivelt Nep Konyvkiado, 1951), p. 184.